On the interchangeability of barrier option pricing models - Visagie, Jaco (South African Statistical Journal, 2018)
An important question when modelling option prices is which of the multitude of option pricing models to use. In this paper, the calculation of barrier option prices is considered. These exotic options are found in many financial markets the world over. It is demonstrated numerically that it is possible to replicate (with a high degree of accuracy) the barrier option prices obtained from one model by making use of a different model; these models are referred to as ‘interchangeable’. Tests for the interchangeability of barrier option pricing models are developed and applied. However, the tests developed are not specific to barrier option pricing models and can also be applied to the prices of other exotic options.